Novel approach to assess seed viability and vigour in Soybean genotypes through Q2 scanning technology: Novel approach to assess seed viability and vigour in Soybean genotypes through Q2 scanning technology - UDAYSREE SHEELA; JHANSI RANI; K P SUJATHA; S NARENDER REDDY (Journal of Oilseeds Research, 2023)
The objective of the study was to establish relationship between seed germination and vigour parameters with an intension to predict the planting value of seed lots of soybean. The variation among genotypes was assessed for quality parameters. Different seed lots of variety JS 335 were analysed for seed quality in Q2 scanner. The vigour parameters estimated through Q2 scanning and conventional methods corresponded with each other. The correlation and regression analysis among germination and vigour parameters were worked out, which indicated significant values with respect to final count of germination and field emergence.